Xun bao zhu luo ji - Xiao, Jiangnan (Beijing, China, China Publishing House Children, 2017)
Dream to become a treasure hunter. with the help of Dave. she pursued the footsteps of grandpa. through the Jurassic eons ago. began a magical treasure-hunt trip. In this era. sunflowers have to find ways to get along with many dinosaurs: Help pony Gate Creek find mother. and sword dragon
Keywords: Comic books, strips, etc -- China; Caricatures and cartoons -- Juvenile literature -- China; Xi you ji -- Caricatures and cartoons -- Juvenile literature